Comparison Of Liver Cell Models Using The Basel Phenotyping Cocktail - Benjamin Berger; Benjamin Berger; Massimiliano Donzelli; Massimiliano Donzelli; Swarna Maseneni; Swarna Maseneni; Franziska Boess; Adrian Roth; Stephan Krähenbühl; Stephan Krähenbühl; Stephan Krähenbühl; Manuel Haschke; et al. (Frontiers Media S.A., 2016)
Currently used hepatocyte cell systems for in vitro assessment of drug metabolism include hepatoma cell lines and primary human hepatocyte (PHH) cultures. We investigated the suit-ability of the validated in vivo Basel phenotyping cocktail (caffeine [CYP1A2], efavirenz [CYP2B6], losartan [CYP2C9], omeprazole [CYP2C19], metoprolol [CYP2D6], midazolam [CYP3A4]) in vitro and characterized four hepatocyte cell systems (HepG2 cells, HepaRG cells, and primary cryopreserved human hepatocytes in 2-dimensional [2D] culture or in 3D-spheroid co-culture) regarding basal metabolism and CYP inducibility. Under non-induced conditions, all CYP activities could be determined in 3D-PHH, CYP2B6, CYP2C19, CYP2D6 and CYP3A4 in 2D-PHH and HepaRG, and CYP2C19 and CYP3A4 in HepG2 cells. The highest non-induced CYP activities were observed in 3D-PHH and HepaRG cells. mRNA expression was at least 4-fold higher for all CYPs in 3D-PHH compared to the other cell systems. After treatment with 20µM rifampicin, mRNA increased 3 to 50-fold for all CYPs except CYP1A2 and 2D6 for HepaRG and 3D-PHH, 4-fold (CYP2B6) and 17-fold (CYP3A4) for 2D-PHH and 4-fold (CYP3A4) for HepG2. In 3D-PHH at least a 2-fold in-crease in CYP activity was observed for all inducible CYP isoforms while CYP1A2 and CYP2C9 activity did not increase in 2D-PHH and HepaRG. CYP inducibility assessed in vivo using the same phenotyping probes was also best reflected by the 3D-PHH model.Our studies show that 3D-PHH and (with some limitations) HepaRG are suitable cell systems for assessing drug metabolism and CYP induction in vitro. HepG2 cells are less suited to as-sess CYP induction of the 2C and 3A family. The Basel phenotyping cocktail is suitable for the assessment of CYP activity and induction also in vitro.